The Tactics and Utilization of Questioning in Kurdish Language: a Pragmatic Study - Ali, Sherzad Sabri; Muhe, Jeehan Ghaiath (Journal of Duhok University, 2019)
Questioning is crucial in language, particularly in pragmatics field. The present study attempts to examine the tactics and utilization of questioning in Kurdish language in order to identify how the speaker is able to fulfil his goals by asking questions. By conducting a descriptive- analytical approach the study attempts to explore how the speaker makes questions in Behdini subdialect and what is the purpose of his questions. The current study has been divided into two parts; the first part is a bout questions in general and the language of meta. The second part discusses the tactics and utilizations of questioning in Kurdish language (Badini).